Family repercussions and social support in relatives of patients with spinal cord injuries - Chávez-Cristóbal, Olinda (2022)
Objective: To determine if there is an association between family repercussions and social support in patients with spinal cord lesions. Methods: An observational study was conducted in a rehabilitation institute of the Ministry of Health including 50 families of patients with spinal cord injuries. Family repercussion was evaluated using the family impact scale (IRFA) and social support was evaluated through the Medical Outcomes Study-Social Support Survey (MOS). Results: 44% of patients and 58% of relatives were in between 30-59 years of age; 34% of caregivers were married with the patient; 62% of families lived in extreme poverty; 78% of patients had paraplegia and 48% had ASIA A lesions. Overall repercussion occurred in 68% and negative repercussions occurred in 94%. Mean social support in emotional/informational, instrumental, affective and positive social interaction was 27.8 ± 4.7, 15.2 ± 2.5, 11.3 ± 1.9, and 12.8 ± 2.4 points, respectively. An association of gender (p=0.043), age of patient (p=0.013) and parental relationship (p=0.014) was found with family repercussion. However, no relationship was found between social support and family repercussions. Conclusions: No differences in social support and family repercussion were found among relatives of patients suffering from spinal cord injuries.